Transnational sports soundscapes: Soccer announcers and radio in Argentina and Chile, 1920s‐60s. (1st April 2021) - Acuña, Pedro
The article contributes to the field of cultural studies and radio history by focusing on soccer (or fútbol), arguably the most significant mass spectacle in twentieth-century Latin America. By exploring the trajectories, iconic voices and styles of sportscasters, the article reconstructs the masculine soundscape of soccer in Argentina and Chile between the 1920s and 1960s. Play-by-play announcers, who ranged from second-rate actors and singers to professional journalists, crafted their own versions of masculinity and nationalism that were central to representing sports culture in an increasingly transnational context. The article pays special attention to the sporting press, audio records and sports films, since many commentators borrowed heavily from other forms of mass culture. Their oral representations of the game, loaded with moral evaluations and political statements, can be seen as cultural texts because they enabled new ways of imagining sports for much larger audiences than those sitting in the stadium.